Evaluation of the Rape Crisis Scotland National Advocacy Project: Final Report - Bradley, Lisa (2018)
This is the final report detailing findings from the evaluation of Rape Crisis Scotland’s National Advocacy Project (NAP). It draws upon data gathered since the launch of the NAP in February 2016 to the end of August 2017. Findings are presented in three main sections: key national stakeholder perspectives; survivor data and perspectives; and practitioner perspectives. Key themes and learning points from the evaluation findings and recommendations for future policy and practice are then identified. A shorter executive summary of this report has also been made available for use as a policy and practice briefing